2013
DOI: 10.1111/jen.12044
|View full text |Cite
|
Sign up to set email alerts
|

Demographic parameters of the two main fruit fly (Diptera: Tephritidae) species attacking mango inCentralTanzania

Abstract: Fruit flies (Diptera: Tephritidae) are among the most important pests damaging fruit crops growing in Tanzania. Demographic parameters for Ceratitis cosyra (Walker) and Bactrocera invadens (Drew, Tsuruta & White) are reported and compared. These include pre‐adult survival and development rates, adult survival and fecundity and population parameters such as the intrinsic rate of increase, and mean generation time. Population and biological parameters of the C. cosyra and B. invadens were measured in an environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…This observation is consistent with earlier studies with other tephritid species (Carey et al 1985, Fletcher 1987, Vargas et al 1996, Vargas et al 1997, Brèvault and Quilici 2000, Duyck and Quilici 2002, Grout and Stoltz 2007, Rwomushana et al 2008, Salum et al 2013, Liu and Ye 2009, Vayssières et al 2008, Vargas et al 2000). However, in the South African Ceratitis rosa populations (R1 and R2), developmental duration of the egg and larva were found to decrease with increasing temperature up to 30 °C, followed by a slight increase in developmental duration beyond 30 °C.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is consistent with earlier studies with other tephritid species (Carey et al 1985, Fletcher 1987, Vargas et al 1996, Vargas et al 1997, Brèvault and Quilici 2000, Duyck and Quilici 2002, Grout and Stoltz 2007, Rwomushana et al 2008, Salum et al 2013, Liu and Ye 2009, Vayssières et al 2008, Vargas et al 2000). However, in the South African Ceratitis rosa populations (R1 and R2), developmental duration of the egg and larva were found to decrease with increasing temperature up to 30 °C, followed by a slight increase in developmental duration beyond 30 °C.…”
Section: Discussionsupporting
confidence: 94%
“…Temperature effects on development and stage-specific survival have been shown to influence both the quantity and quality of tephritid fruit flies produced (Vargas et al 1996, Vargas et al 1997, Brévault and Quilici 2000, Vargas et al 2000, Duyck and Quilici 2002, Trudgill et al 2005, Grout and Stoltz 2007, Rwomushana et al 2008, Vayssières et al 2008, Liu and Ye 2009, Salum et al 2013). Various tephritid species have specific optimal temperature range for development limited by lower and upper thresholds (base temperature and upper limit).…”
Section: Introductionmentioning
confidence: 99%
“…In Benin, Vayssières et al (2005) reported a decrease in density of Ceratitis cosyra as the density of Bactrocera dorsalis increases. The evidence of competitive displacement of Ceratitis cosyra by Bactrocera dorsalis was provided by Ekesi et al (2009) with Bactrocera dorsalis having stronger competitive traits than Ceratitis cosyra (Salum et al 2013). The latter is now mostly confined to hosts of the family Annonaceae in this study area (Geurts et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a very large host range for B. invadens compared with that of C. cosyra (a dozen hosts in Benin), the Asian fly species also has other important comparative advantages vs. the native species. Biological advantages are the shorter length of immature stages and also longer life span fecundity for B.invadens vs. C. cosyra [47]. Other advantages include behavioral traits, including its dispersal, since the exotic species is a strong flyer able to move about 10 km per week, contrary to the native fly (Vayssières et al, pers.…”
Section: Discussionmentioning
confidence: 99%